2015
DOI: 10.1021/acs.jpcb.5b03553
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Residence Time of Water around DNA Base Pairs: Governing Factors and the Origin of Heterogeneity

Abstract: Water dynamics in the solvation shell around biomolecules plays a vital role in their stability, function, and recognition processes. Although extensively studied through various experimental and computational methods, dynamical time scales of water near DNA is highly debated. The residence time of water is one such dynamical quantity that has been probed rarely around DNA using computational methods. Moreover, the effect of local DNA sequence variation in water residence time has also not been addressed. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 84 publications
7
36
1
Order By: Relevance
“…It has been reported that the behavior of water molecules and water structure around proteins is quite regular. However, there is heterogeneity in the behavior of water molecules around DNA [ 66 ]. Different groups and studies have reported different residence time for the water molecules in the grooves of DNA which varies from 200 ps to 1 ns [ 67 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the behavior of water molecules and water structure around proteins is quite regular. However, there is heterogeneity in the behavior of water molecules around DNA [ 66 ]. Different groups and studies have reported different residence time for the water molecules in the grooves of DNA which varies from 200 ps to 1 ns [ 67 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…This clearly evidences the restricted dynamics of water molecules in the close vicinity of DNA. This retardation relative to bulk water (up to a 6-fold slowdown at room temperature) is due to interactions of the water molecules with hydrophobic moieties and phosphate groups of the biopolymer, 49,62 a small number of particularly slow water molecules having been found in DNA's minor groove (bridging the nitrogen and oxygen atoms of complementary bases), with reorientation times between 60 and 85 ps -the so-called ''spine of hydration''. 63 In addition, the lower residence times presently measured for drug-incubated DNA may be partially due to a charge screening effect of the metal complexes under study (comprising partial positive charges on the Pt(II) and Pd(II) ions), that may weaken the electrostatic interactions between hydration water and negatively charged phosphates at the DNA surface, thus allowing increased flexibility of the system.…”
Section: Qensmentioning
confidence: 99%
“…The non-equilibrium response functions S(t) for the charge extinction and creation cases for the solute and water solvent model we have used 29 shown in Fig.1 that found by MF for a similar but somewhat different model, but -as discussed further below-are mute on the molecular interpretation. The importance of obtaining an appropriate molecular interpretation is emphasized not only by the non-linear response aspect mentioned above, but also, and more generally, by the key role in hydrogen-bonded water molecular dynamics in a host of charge transfer chemical reactions and related phenomena [32][33][34][35][36][37][38][39][40][41][42][43][44][45] . We recently made a first attempt 29,30 to examine this question via a different approach; we employed a work/power or energy flow perspective for solvation dynamics following electronic excitation of a solute 28 , which is an extension to this arena of the corresponding perspective to energy flows to the solvent following solute vibrational excitation 46,47 .…”
Section: Introductionmentioning
confidence: 99%